IL-6 Transsignaling in Patients with Chronic Spontaneous Urticaria. - Alicja Kasperska-Zajac; Alicja Grzanka; Aleksandra Damasiewicz-Bodzek (PLoS ONE)
Background IL-6 trans-signaling is critically involved in the initiation and promotion of inflammatory and autoimmune diseases. Therefore, we investigated the clinical relevance of soluble members of IL-6 trans-signaling system in chronic spontaneous urticaria (CSU). Methods IL-6, interleukin 6 soluble receptor (IL-6 sR) and soluble gp130 (sgp130) were measured by ELISA method in plasma from CSU patients and the healthy subjects. The data were related to activation of the acute phase response as indicated by serum C-reactive protein (CRP) concentration and compared between patients stratified by the disease activity. Results Concentrations of IL-6, IL-6 sR, sgp130 in plasma and CRP in serum were significantly elevated in CSU patients compared with the healthy controls. CRP correlated significantly with IL-6 and sgp130, similarly IL-6 correlated significantly with sgp130. By contrast, CRP and IL-6 did not correlate significantly with IL-6 sR. However, significant correlation was noted between IL-6 sR and sgp130. Conclusions Concentrations of IL-6 and its soluble receptors were significantly elevated in patients with CSU, suggesting upregulation of the IL-6 trans-signaling in the disease. In addition, our results support the concept that the system may be involved in pathogenesis of the systemic inflammatory activation in CSU patients.